Development of Gefitinib-Loaded Solid Lipid Nanoparticles for the Treatment of Breast Cancer: Physicochemical Evaluation, Stability, and Anticancer Activity in Breast Cancer (MCF-7) Cells - Ibrahim A. Aljuffali; Md. Khalid Anwer; Mohammed Muqtader Ahmed; Ahmed Alalaiwe; Mohammed F. Aldawsari; Farhat Fatima; Shahid Jamil (MDPI AG, 2023)
In the current study, the toxic effects of gefitinib-loaded solid lipid nanoparticles (GFT-loaded SLNs) upon human breast cancer cell lines (MCF-7) were investigated. GFT-loaded SLNs were prepared through a single emulsification-evaporation technique using glyceryl tristearate (Dynasan™ 114) along with lipoid® 90H (lipid surfactant) and Kolliphore® 188 (water-soluble surfactant). Four formulae were developed by varying the weight of the lipoid™ 90H (100-250 mg), and the GFT-loaded SLN (F4) formulation was optimized in terms of particle size (472 ± 7.5 nm), PDI (0.249), ZP (−15.2 ± 2.3), and EE (83.18 ± 4.7%). The optimized formulation was further subjected for in vitro release, stability studies, and MTT assay against MCF-7 cell lines. GFT from SLNs exhibited sustained release of the drug for 48 h, and release kinetics followed the Korsmeyer-Peppas model, which indicates the mechanism of drug release by swelling and/or erosion from a lipid matrix. When pure GFT and GFT-SLNs were exposed to MCF-7 cells, the activities of p53 (3.4 and 3.7 times), caspase-3 (5.61 and 7.7 times), and caspase-9 (1.48 and 1.69 times) were enhanced, respectively, over those in control cells. The results suggest that GFT-loaded SLNs (F4) may represent a promising therapeutic alternative for breast cancer.